Endomembrane remodeling in autophagic membrane formation. Issue 5 (4th May 2018) - Zhang, Min; Wang, Yu; Ge, Liang
ABSTRACT: Autophagosomal membrane sources generate autophagic membrane precursors, which later assemble into the double-membrane autophagosome. The key events happening on the membrane sources during autophagic membrane generation remain poorly characterized. Our previous work found the ER-Golgi intermediate compartment (ERGIC) as a membrane source for the phagophore, the precursor to the autophagosome. A relocation of the COPII machinery from the ER-exit sites (ERES) to the ERGIC generates vesicles for LC3 lipidation. In recent work, we made a further step by showing that a starvation-induced remodeling of ERES facilitates the relocation of COPII to the ERGIC and the generation of the autophagic membrane.